(untitled) (Biological Sciences - PJSIR, 2004)
Twenty - eight seed samples of eight oats (Avena sativa L.) cultivars were collected from Sargodha, Faisalabad and Bahawalpur districts of the Punjab, Pakistan during 1999 - 2000 and analyzed for seed - borne mycoflora during 2000 - 2001. Four genera and nine species of fungi were identified at different frequencies. Drechslera avenae and D. sorokiniana, known pathogens causing pre - and post - emergence seedling blight and leaf spot in mature plants were detected in 67.80 and 53.60% of the seed samples with maximum infection of 34.00 and 6.00%, respectively. Phoma sp. was found in 46.40% of the sample with a maximum infection of 16.00%. Phoma is a new pathogen recorded on oats in Pakistan. All these fungi were found equally pathogenic and caused 86.00, 67.80 and 86.70% pre - and post - emergence seedling mortality in pathogenicity test. These pathogens produced almost the same type of symptoms on roots and leaves. In two samples Cephalosporium sp. was recorded in high frequencies (up to 66.00%) but did not show any pathogenic effect on seeds and seedlings. The observed association of different fungi with oats seeds in the present study indicates the need of thorough survey for these and other pathogenic fungi.